2016
DOI: 10.1155/2016/1017524
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Presentation of Gianotti-Crosti Syndrome due to Epstein-Barr Virus Infection

Abstract: Gianotti-Crosti syndrome (GCS) is viral exanthema of childhood. It typically presents with a symmetric erythematous papular and papulovesicular eruption. It has been classically associated with hepatitis B virus, as well as rarely with Epstein-Barr virus (EBV). We report a case of GCS related to EBV infection without the classical systemic symptoms in a five-year-old male patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…It is a relatively common condition worldwide, but frequently remains underdiagnosed. It appears most commonly in infants between 1 and 6 years old, however similar cases were described in adults [ 1 , 4 ]. Studies showed that GCS occurred more frequently during spring and summer and in patients with personal or family history of atopy [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 90%
“…It is a relatively common condition worldwide, but frequently remains underdiagnosed. It appears most commonly in infants between 1 and 6 years old, however similar cases were described in adults [ 1 , 4 ]. Studies showed that GCS occurred more frequently during spring and summer and in patients with personal or family history of atopy [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 90%
“…We found 264 studies related to the possible cutaneous and mucosal manifestations during EBV acute infection; we selected the articles that more exhaustively reported the clinical and laboratory description of the case/cases, 5‐45 published from 1954 to 2018 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The immunopathogenic mechanism of GSC is still obscure. While historically thought to be a manifestation of hepatitis B infection, the association with various viral agents (Coxsackie, CMV, enteroviruses, parvovirus B19, poxvirus, rotavirus, rubella, hepatitis A virus, HSV-1) has been reported and, not rarely, GCS has been described following vaccination (3)(4)(5)(6). This suggest a role of an immunologic response to viral antigens rather than a primary manifestation of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although often asymptomatic, the lesions may be mildly to moderately pruritic. It is known or suspected to be associated with many viral infections, such as Hepatitis B virus, Cytomegalovirus, Coxsackie, Adenovirus, Influenza and, more frequently, Epstein-Barr virus (3,4). Recent immunizations are often described in association to GCS (5,6).…”
Section: Introductionmentioning
confidence: 99%